A cross-sectional study on dietary assessment, oral hygiene behavior, and oral health status of adolescent girls - Mahriani, Yuni; Indriyanti, Ratna; Musnamirwan, Iwan Ahmad; Setiawan, Arlette Suzy (Frontiers in Nutrition, 2022)
Adolescents are a population group that is vulnerable to nutritional problems other than toddlers, especially young women. Special attention to the dietary issues of adolescent girls needs to be obtained along with the increase in the adolescent population in Indonesia because this affects the growth and development of the body and will impact adult nutrition problems. The purpose of the study was to analyze the relationship between diet assessment and oral health status of adolescent girls, the relationship between oral hygiene behaviour and oral health status of adolescent girls, and the simultaneous relationship between dietary assessment and oral hygiene behaviour with the oral health status of adolescent girls. Analytical research using the survey method was conducted on 96 young women in two junior high schools in Bandung. Assessment of diet seen from eating behaviour and anthropometric examination. Eating behaviour using the Adolescent Food Habit Checklist Index questionnaire and anthropometric investigations were carried out by looking at body height, body weight, and Mid Upper Arm Circumference using the standards from the Indonesian Minister of Health Regulation 2020. Oral hygiene behaviour using the Oral Hygiene Behavior Index questionnaire. Oral health status using the Dental Health Status Assessment. The results were statistically analyzed with Spearman's Rank Correlation, and Multiple Linear Regression tests showed no significant relationship between dietary assessment and oral health status (eating behaviour with a p-value = 0.429 and anthropometric examination with a p-value = 0.262). A significant association between oral hygiene behaviour and oral health status, with a p-value of 0.003, while there is no simultaneous relationship between diet assessment and oral hygiene behaviour with oral health status, with multiple r2=13.2%.